Combination of maghemite and titanium oxide nanoparticles in polyvinyl alcohol-alginate encapsulated beads for cadmium ions removal - Majidnia, Zohreh (Springer New York LLC, 2015)
Both maghemite (?-Fe2O3) and titanium oxide (TiO2) nanoparticles were mixed at various ratios and embedded in polyvinyl alcohol (PVA)-alginate beads. These beads were tested for photocatalytic behavior in eliminating toxic Cd(II) from the aqueous solution. The photocatalytic experiments were performed under sunlight irradiation at various pH, initial feed concentrations and ?-Fe2O3: TiO2 ratios. The recycling attribute of these beads was also investigated. The results revealed that 100% of the Cd(II) was eliminated in 150 minutes at pH 7 under sunlight. It shows that maghemite and titania PVA-alginate beads can be readily isolated from the aqueous solution after the photocatalyst process and reused for at least six times without losing their initial properties.